Pendidikan Islam dan Ketahanan Sosial Santri di Lingkungan Padat Penduduk: Perspektif dari Pondok Pesantren Darul Ulum Palangka Raya - Musfi Musfi; Muhammad Hoiri Ulfi (Journal of Innovative and Creativity, 2025)
This study aims to examine the role of Islamic education in building social resilience among student at Islamic Boarding School Darul Ulum, located in the densely populated and multi-ethnic neighborhood of Gang Puntun, Palangka Raya. While previous studies have explored social resilience in general, there is a gap in understanding how Islamic education in Islamic Boarding School contributes to strengthening social resilience in urban environments with complex social challenges. The research employs a qualitative approach, using in-depth interviews, participatory observation, and document analysis involving students, Islamic Boarding School leaders, and local community members. The findings indicate that Islamic education, through the internalization of moral values, disciplined routines at the Islamic Boarding School, and active community engagement, plays a crucial role in shaping social resilience, strengthening inter-community relationships, and addressing social challenges such as drug abuse. The implications of this study suggest that Islamic education in Islamic Boarding School not only focuses on religious learning but also plays a key role in building inclusive communities that are resilient to social issues. Further research is expected to expand understanding of the application of Islamic education in urban and multicultural contexts.